Preparing Performance Reports for Upper Management: A Skills Building Project for Sales Management Students - Chapman, Joseph D.; Zeiss, Jessica G.; Wahlers, Russell G. (American Journal of Management, 2020)
This paper presents an in-depth assignment used in sales management courses to help students develop the skills needed to prepare a formal performance report for upper management. Students are divided into district management teams and are required to prepare a company performance report for four years of their company’s performance. The author provides the detailed guidelines which are given to the students to aid them in the development of the performance report. Example tables for the report, the grading process, and other information for the project are also included.